ANALISIS KOMUNIKASI INTERPERSONAL DALAM PEMBENTUKAN AKHLAKUL KARIMAH - Agus Baihaqi; Dwi Kusnia Mubarokah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Abstract This study aims to determine: interpersonal communication between the management and students in the process of guiding morality, effective interpersonal communication between the administrators and students, and the inhibiting factors of interpersonal communication between the management and students at the Sunan Ampel Islamic Boarding School Bangorejo. This study uses a Nuturalistic approach, which aims to seek and find meaning or understanding of phenomena in a special contextual setting. Data collection strategies through observation, interviews, and documentation, as well as data validity include validity testing with source and theory triangulation. The results of research conducted at the Sunan Ampel Islamic Boarding School Bangorejo, in the process of guiding the formation of morality, used an interpersonal communication approach. And indications of successful interpersonal communication that administrators have, in particular: can encourage approval, excitement, mental changes, good connections, and lead to activity. Furthermore, the suppressive variables of interpersonal communication, including the mental state of communication, one-way messages, and verbalistic message recognition, etc. Abstrak Penelitian ini bertujuan untuk mengetahui : Komunikasi interpersonal pengurus dengan santri dalam proses pembimbingan akhlaqul karimah, komunikasi interpersoal yang efektif antara pengurus dengan santri, dan faktor-faktor peghambat komunikasi interpersonal pengurus dengan santri di Pondok Pesantren Sunan Ampel Bangorejo. Penelitian ini, menggunakan pendekatan naturalistik, yaitu bertujuan untuk mencari dan menemukan pengertian atau pemahaman tentang fenomena dalam suatu latar yang berkonteks khusus. Strategi pengumpulan data melalui observasi, wawancara dan dokumentasi, serta validitas data meliputi uji validitas dengan triangulasi sumber dan teori. Adapun hasil penelitian yang dilakukan di Pondok Pesantren Sunan Ampel Bangorejo dalam proses pembimbingan pembentukan akhlaqul karimah, menggunkan pendekatan komunikasi interpersonal. Dan indikasi komunikasi interpersonal yang berhasil yang dimiliki pengururs, khususnya : Dapat mendorong persetujuan, kegembiraan, Perubahan mentalitas, koneksi yang lebih baik, dan mengarah pada aktivitas. Selanjutnya, variabel penekan komunikasi interpersonal, termasuk kondisi mental komunikan, pesan satu arah, dan pengenalan pesan verbalistik, dan lain-lain.